Pancreas Transplantation From Pediatric Donors: A United Network for Organ Sharing Registry Analysis. Issue 10 (October 2017) - Spaggiari, Mario; Bissing, Martha; Campara, Maya; Yeh, Chun-Chieh; Tzvetanov, Ivo; Jeon, Hoonbae; Benedetti, Enrico
Abstract : Background: Pancreas grafts from pediatric donors are still considered "not ideal." Perceived concerns are related to low islet mass and potential for graft thrombosis. Methods: The study evaluated all pancreas transplants from January 2000 to May 2015 using the Organ Procurement and Transplant Network database. Comparative analysis of recipient and graft survival was performed between pediatric (⩽18 years) and adult donors. In the pediatric group, the outcomes were stratified based on donor age (⩽6, 7-12, and 13-18 years) and weight (<30, 30-95, and >95 kg). Results: In the selected era, 18 430 pancreas transplants were performed from 4915 pediatric donors (27%). Short-term graft and patient survivals were comparable between pediatric and adult donors. Ten-year patient and graft survivals were higher in the pediatric donor group: (70% and 54% vs 68% and 51%, P = 0.001). However, very-low-weight pediatric donors (<30 kg) resulted in worse graft survival in the long term (44% at 10 years, P = 0.006). Conclusions: Pediatric donor pancreas transplants had comparable patient and graft survival to the adult donor transplants. However, the islet mass of very small donors could influence long-term graft survival if the weights of donors and recipients are not properly matched. Usage of "very small" pediatric donors was not associated with higher incidence of technical complications or early graft loss. Abstract : Pediatric donor pancreas transplants have comparable patient and graft survival to the adult donor transplants and utilization of "very small" pediatric donors are not associated with higher incidence of technical complications or early graft loss.